The Spiritualization of Arabic Grammar: Theological Meaning-Making of Nahwu in a Salaf Pesantren in Indonesia - Rohman, Abdul; Maksum, Ali; Wargadinata, Wildana (Teosofi: Jurnal Tasawuf dan Pemikiran Islam, 2025)
This article examines how Arabic grammar (nah}wu) is theologically reinterpreted as a medium for ethical and spiritual formation within a Salaf pesantren in Indonesia. In response to contemporary moral challenges confronting pesantren communities, the study explores a pedagogical approach known as Spiritual Nah}wu, developed at Pondok Pesantren Babussalam Pagelaran. Employing a phenomenological–hermeneutical methodology, the research analyzes how kiai and ustādh reconfigure nahwu from a technical–linguistic discipline into a spiritually grounded epistemology oriented toward tazkīyat al-nafs. Drawing on in-depth interviews, participant observation, and textual analysis, the findings demonstrate that grammatical categories are interpreted as symbolic representations of moral and spiritual states, enabling nah}wu to function as a mode of theological meaning-making and ethical internalization. This pedagogical model integrates cognitive, affective, and spiritual dimensions of learning, thereby challenging the modern separation between knowledge and morality. The article contributes to scholarship on Islamic education by illustrating how auxiliary Islamic sciences can serve as sites of epistemic agency and decolonial knowledge production rooted in pesantren traditions.